2017
DOI: 10.18203/2320-6012.ijrms20170172
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of morbidity pattern among rural and urban postmenopausal women of Allahabad, Uttar Pradesh, India

Abstract: Background: Menopause is an inevitable reproductive phase during midlife when various physical and mental changes may impair the quality of life of women. Middle-aged women may experience a wide range of physical and psychological symptoms. Decrease in the production of estrogen leads to the premenopausal symptoms of hot flushes, insomnia and mood changes, as well as post-menopausal osteoporosis and vaginal atrophy, leading to decrease in quality of life.Methods: Community based cross-sectional study. Door to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
6
3
Order By: Relevance
“…This was 4.0% in urban women (11) and 3.3% in the rural population (4). Symptoms related to urinary tract comprised of 12.3% in this study which was less than that reported in a rural population (4).…”
Section: Discussioncontrasting
confidence: 68%
“…This was 4.0% in urban women (11) and 3.3% in the rural population (4). Symptoms related to urinary tract comprised of 12.3% in this study which was less than that reported in a rural population (4).…”
Section: Discussioncontrasting
confidence: 68%
“…in Allahabad reports a lower prevalence of vasomotor symptoms (34.5% vs. 39.5%) and a higher prevalence of physical symptoms (e.g., joint pain, 57% vs. 55.5%) and stress incontinence (10.5% vs. 8.5%) among rural women in comparison to urban women. [ 12 ] A study by Nayak et al . in rural Karnataka reported a higher proportion of physical symptoms, namely, feeling tired and worn out (67.5%), decreased physical strength (63.6%) and decreased stamina (64%) and psychosocial symptom like poor memory (73.7%); hot flashes were present in 32% while decrease in sexual desire was reported in 26.8%.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the findings of Poomalar and Arounassalame, Nayak et al ., and Goyal et al ., but not with that of Sharma and Mahajan. [ 12 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Menopausal age of Caucasian women is reported between 48 and 55 years, usually occurs earlier in Indian women, the average age being between 40 and 49 years. [ 1 ] Recent studies across the world have thrown light on the increased cardiometabolic risks in postmenopausal women as compared to their corresponding premenopausal counterparts. [ 2 3 ] Postmenopausal women may be predisposed to increased cardiovascular risks, possibly due to depletion in the ovarian follicles followed by subsequent reduction in estradiol concentrations.…”
Section: Introductionmentioning
confidence: 99%